The influence of tobacco and alcohol in oral cancer: literature review - Rafaella B. Leite; Ana Carla O. Marinho; Beatriz L. Costa; Maria Beatriz V. Laranjeira; Kleyber D. T. Araújo; Anaícla F. M. Cavalcanti
ABSTRACT In Brazil, smoking and drinking are more common in male patients, less frequently affecting female patients. The most diagnosed type of lesion is squamous cell carcinoma. This article aims to understand the literary references associated with the influence of tobacco and alcohol on the development of oral cavity cancer. In order to elaborate an analytical and thematic literature review, using the Literatura Latino-Americana e do Caribe em Ciências da Saúde (Lilacs), Scientific Electronic Library Online (Scielo), US National Library of Medicine National Institutes of Health (PubMed) and Medline databases, articles from the English and Portuguese literatures published between 2007 and 2019 were searched with the help of the terms: prognostic factors and indicators, tobacco, alcohol and oral carcinoma. Proper knowledge of the disease and its etiological and prognostic factors should make professionals able to prevent, identify and control oral cancer.